Climate change, supply chain management, and enterprise adaptation implications of global warming on the economy - Pappis, Costas P. 1945- (Information Science Reference, 2010)
"This book provides an interdisciplinary treatment of issues raised by climate change in connection with its implications for society, environment and economy, particularly at the company and the supply chain levels"--Provided by publisher.